Prilozi metodologiji vrednovanja knjižničnih zbirki - Petr Balog, Kornelija (Knjižnica, 2020)
Purpose: This paper presents various methods of evaluation of library collections and points out their advantages and disadvantages, as well the situations in which a cer-tain method is usually applied. Library collections make the foundation of library ser-vices and therefore must be of high quality and continuously evaluated in relation to user needs. This paper gives overview of methods and techniques used for evaluation of library collections with the goal to make this necessary segment of evaluation in libraries easier for librarians. It is necessary to point out at this place that the paper focuses on the evaluation methods and techniques of the traditional library materials.Methodology/approach: The paper analyses various methods and techniques for evalu-ation of library collections. Results: The analysis of various methods and techniques has revealed that there is no ideal or uniquely appropriate approach for evaluation and that the best way is to use the combination of several (qualitative and quantitative) methods.Research limitations: The paper presents a selected set of most frequently used meth-ods and techniques for evaluation, whereas those less frequently used methods are left out from this review.Originality/practical implications: Evaluation of library collections is an extremely ef-fort- and time-consuming task, which librarians perform reluctantly and rarely. At the same time, the evaluation results are of extreme importance for the perception of qual-ity of the library and the evaluation itself should be carried out continuously and regu-larly. This paper is expected to bring the topic of evaluation of library collection closer to librarians and motivate them to perform more frequent activities in this direction.
Keywords: knjižnice; knjižnične zbirke; knjižnično gradivo; metodologija; vrednotenje